Technology for obtaining anomalous photovoltaic effect films from cadmium halides and on the nature of Microphotocells - Onorkulov, K.; Zokirov, A. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2023)
This article discusses the technology of obtaining anomalous photovoltaic (APV) effect films from cadmium halides. APV effect is a unique phenomenon where a photo-induced voltage is generated across a metal-semiconductor interface, and it has been a subject of research for decades due to its potential applications in solar energy conversion devices. In this context, cadmium halides are a promising class of materials for APV effect films due to their unique properties. The technology of obtaining APV effect films from cadmium halides involves a complex process of film deposition, annealing, and surface modification, followed by a series of electrical and optical measurements to characterize the material properties. This article highlights the recent advancements in the technology of APV effect films from cadmium halides, including the use of new deposition techniques, surface modification approaches, and device architectures. The potential applications of these films in solar energy conversion devices are also discussed, along with the challenges and opportunities in the field of APV effect research.